(untitled) (Medical Forum Monthly, 2020)
Objective: The main objective of the study is to determine the diagnostic accuracy of MRI for diagnosis of rotator cuff tear in patients presented with shoulder pain. Study Design: Cross-sectional study Place and Duration of Study: This study was conducted at the conducted in the department of radiology, Mayo Hospital Lahore for 6 months i.e. Feb 2019 to Feb 2020. Materials and Methods: At that point patients were go through MRI. Multi-planar MR imaging of the shoulder was performed utilizing coronal slanted proton thickness, coronal sideways T1 weighted, coronal diagonal T2 weighted with fat immersion, sagittal angled T2-weighted with fat immersion, and hub T2 weighted arrangements. Results: The mean age of the patients was 50.01±11.28. There were 62(41.3%) males and 88 (58.7%) females in our study. The mean tear size was 3.15±1.42 cm. Sensitivity and specificity of MRI for the diagnosis of 3 rotator cuff injuries was 90.67% and 96.00%. However, PPV and NPV values for MRI was 95.77% and 91.14% respectively. Overall diagnostic accuracy of MRI for the diagnosis of rotator cuff tear in patients presenting with shoulder pain. Conclusion: Results of this study showed that diagnostic ability of MRI is excellent in diagnosing rotator cuff tear in patients presented with shoulder pain.